Best practices and constraints in Geopark Management: comparative analysis of two Spanish UNESCO Global Geoparks - Canesin, Thais de Siqueira (2020)
Spain is an international reference for geoparks and geoconservation polices, and it is the second country in the world with the highest number of UNESCO Global Geoparks (UGGps), after China. Additionally, Spain was one of the four countries involved in the establishment of the European Geoparks Network (EGN) in 2000, the first geoparks network. Based on this prominent role of Spain, the present research had the aim to analyse and characterize the process of establishment, development, and manage- ment of two Spanish UGGps. This study also intended to identify important aspects of the operation and management that can be a reference to other geoparks. As geological heritage is one of the essential requirements of any geopark, geoconservation has particular importance in the geopark management, requiring experts in the geopark staff. Equally important is that the manage- ment structure can effectively ensure an integrated development of the territory, connecting the geopark staff, the whole com- munity, and the stakeholders. A good cooperation of the management team with the administration of protected areas that might exist within a geopark is also noteworthy, because park managers have extensive experience in the implementation of nature conservation and environmental education actions, activities that can certainly benefit any geopark.